Prototyping and Performance Evaluation of Fire Rated Acoustic Door - Khalid, Muhammad Haziq; Abd Rahman, Ramhuzaini; Abdul Latif, Hanif; Yahya, Musli Nizam (International Journal of Integrated Engineering, 2018)
In recent years, demands to install the fire rated doors with acoustic absorption capability in Malaysia industrial buildings are growing than ever. This may possibly be achieved by integrating the Fire Rated and Acoustic Doors into a single door consisting of sound and fire resistance features called Fire Rated Acoustic Door (FRAD). However, performance of the door is still yet to be investigated as it depends on the applied internal core material. This paper presents development of two FRAD prototypes including performance evaluation on the fire rating and sound transmission classification (STC). The first prototype applies sandwich Gypsum-Rockwool-Gypsum board as its internal core while the second uses Magnesium Oxide-Rockwool-Magnesium Oxide. The door leaf and frame are made from the standard galvanized iron. The fire rating test was conducted using procedure that satisfies Malaysian Standard requirement for Fire Rated Door. The STC was estimated through calculation of the transmission loss. Result shows that the developed FRAD of prototype one and two are both capable of holding integrity and insulation of the door structure when expose to fire of up to 180Â°C for about 53 and 120 minutes, respectively. In terms of STC, the FRAD of prototype one and two were calculated to have STC-40 and STC-42, respectively. Note that, the standard minimum requirements of FRAD that need to be achieved in this project are to have at least one hour rating of fire and STC-35 rating in sound resistance. Therefore, the results show that both FRAD prototypes can be utilized for acoustic door function as the STC rating is greater than the minimum requirement. In case of fire protection capability, only FRAD of prototype two exceeds the minimum fire rating. This suggests that only prototype two is possible to be implemented as FRAD as it fulfilled both the fire rating and STC requirements.